Retracted: Challenges faced by women after repair of genital tract fistula: An observational study in Tanganika Province, Democratic Republic of Congo - Notia, Christine Amisi; Philibert, Aline; Mukwege, Denis Mukengere (Nepal Journal of Obstetrics and Gynaecology, 2018)
On 6th February 2020 the Editorial Board of Nepal Journal Obstetrics and Gynaecology agreed to retract the Abstract ‘Challenges faced by women after repair of genital tract fistula: An observational study in Tanganika Province, Democratic Republic of Congo' published in Nepal Journal of Obstetrics and Gynaecology, Vol.13(2) 2018 (DOI: https://doi.org/10.3126/njog.v13i2.21914 ). This retraction was requested by the authors: C.A. Notia, A. Philibert and D.M. Mukwege. We apologise for any inconvenience. This retraction notice appears in Vol.14(1) 2020 DOI: https://doi.org/10.3126/njog.v14i1.27572